MXene-Assisted Enhanced Electrochemical Performance of Doped Strontium Titanium Nanoparticles - Muhammad Qaiser Manzoor; Syed Irfan; null Anwar-ul-Haq; Xuyang Shi (Journal of Nanotechnology)
The growing demand for energy storage has drawn considerable attention to devices such as supercapacitors, which currently lack high energy density but depict high power density and long cycle life. In this work, we have synthesized La0.3Sr0.7Ti0.5Fe0.5O3 (LSTF) nanoparticles and Ti3C2-MXene-modified LSTF nanoparticle hybrid to study the effect of MXene on electrochemical properties of the nanoparticles. The X-ray diffraction (XRD) and Raman spectroscopy analysis showed that the hybrid structure retained all the major peaks of the nanoparticles and the MXene, which showed its successful synthesis. The morphological analysis was done utilizing scanning electron microscopy (SEM), which verified that the nanoparticles had been adsorbed and/or agglomerated onto the MXene sheets. The electrochemical analysis showed that with the addition of MXene into the nanoparticles, the specific capacitance tested via cyclic voltammetry increased from 225.6 Fg‒1 to 419.5 Fg‒1 at the scan rate of 2 mVs-1, which makes the hybrid a suitable electrode material for supercapacitors. The value of specific capacitance for the hybrid tested via galvanostatic charge-discharge showed an increased value of 23 Fg‒1 at the current density of 1 Ag-1. The Fourier transform infrared (FTIR) spectroscopy showed that the hybrid contains –O functional groups coming from MXene, which causes an increase in electrochemical activity at the electrode surface, resulting in enhanced capacitance.